Pemanfaatan Getah Karet Pada Aspal AC 60/70 Terhadap Stabilitas Marshall Pada Asphalt Treated Base (Atb) - Amal, Andi Syaiful (Media Teknik Sipil, 2011)
Road is the prime medium of land transportation that consists of some material like hasrh agregate, smooth agregate, filler, bitumen and also additive materials with certain percentage. Latex is one of additive material that able to be used. The aim of this research is to know about the influence of Latex additition to nature of mixture at Asphalt Treated Base. The mixture planning (mix job) which is gotten from this research is harsh agregate equal to 47,10%, sand equal to 24,03%, stone ash equal to 24,03% (comparison 1 : 1) and filler 4,84%. From this mix job, it is made 60 object test that has rate variation of asphalt 0% - 6% without using Latex. The form of these objects is cylinder. Their measurement is diameter 10 cm, height 7,5 cm and volume 1200 gram. The result of Latex and asphalt mixing shows that the influence of Latex is very real to the stability parameter, irrigate void, flow and Marshall Quotient Optimum Rate Latex is equal to 2,5% with optimal asphalt rate is equal to 3,7%.Keywords : asphalt AC 60/70, Latex